DETERMINATION OF OPTIMUM DOSE OF MIXING WASTEWATER WWTP (WAST WATER TREATMENT PLANT) WITH HOT WATER PRODUCTION LEMATANG RIVER AS OF PARAMETERS PH, CONDUCTIVITY, TURBIDITY, AND SILICA USE COAGULANT PAC IN PT.X - Amiliza Miarti (Bajang Institute, 2023)
Water rivers Lematang commonly used by the community to meet the needs of households and industry around the region . The industry that uses Lematang river water is PLTU as its raw material for production . Apart from that, PLTU also produces liquid waste. The liquid waste comes from ( wast water treatment plant ) which can still be utilized because it has a turbidity value that is still below the max 5 NTU and the pH is still between 6 to 9 . Regarding this,power plant power plant Banjarsari apply the principles of waste control carefully and integrated namely Systems Wastewater Treatment ( Waste Water Treatment Plant ) . In the processing process, it acts as a purifier for a mixture of Lemaang river water and wastewater. Menggunakan coagulant (Poly Aluminum cloride) so it can be reused as water the additional production. The results showed that the mixture of lematang river water with waste water (wast water treatment plant) was 60% : 40% , this indicates the use of the optimum dose as production water. waste water can be used as additional water to be used as production water because the pH value is 7.65; conductivity 187.6; turbidity 4.45; and silica 1.92 . Based on the results of research by utilizing river water and waste water the most effective is the dose ratio of 60%: 40% .